Frontiers of Real Estate Science in Japan - Asami, Yasushi; Higano, Yoshiro; Fukui, Hideo; Asami, Yasushi; Higano, Yoshiro; Fukui, Hideo (Springer Nature, 2021)
This open access book presents recent research and hot topics in the field of real estate science in Japan. It features carefully selected English translations of peer-reviewed papers and excellent articles published in the Japanese Journal of Real Estate Sciences, as well as papers presented at the Japan Association of Real Estate Sciences (JARES) annual conference. The topics covered include market analyses of vacant houses, policies for reuse of vacant houses, property tax policy, issues of land for which the owners are unknown, disaster and real estate values, the siting optimization plan and its influence on real estate, big data and ICT technology for the real estate business, and public real estate management. Real estate science in Japan has developed in step with international research in the fields of law and economics, regional science, civil engineering, environmental science, architectonics, and related areas. At the same time, it has evolved into a unique discipline that focuses on policy-oriented practical science with arguments for the reform of outdated laws, regulations, and traditional customs. Asian countries are currently growing rapidly and are catching up with developing countries. The lessons learned and know-how accumulated by JARES is helpful for practitioners and policymakers not only in Japan, but also in other Asian countries.
English
Keywords: International economic & trade law; Urban economics; Constitutional & administrative law; Public administration; Sales & marketing; Law and Economics; Urban Economics; Administrative Law; Public Policy; Marketing; Regional and Spatial Economics; Real Estate; Japan; Social System; Environment; Market; House; Public international law: economic & trade; Company, commercial & competition law: general; Constitutional & administrative law: general; Public administration; Sales & marketing; Market research